Ifá, Polygyny and Gender Politics: Interpreting Ambivalence in Yorùbá Marriage Culture - ALABEDE, Yetunde S.; BELLO, Temitope Lanre (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This paper offers a critical reframing of polygyny in Yorùbá society by examining Ifá not as a doctrinal authority but as a philosophical archive that illuminates the coexistence of moral ambiguity, gendered power, and cultural hybridity. Rather than treating polygyny as a fixed “tradition,” this paper positions it as a site where religious syncretism, patriarchal politics, and modern identity-making intersect. Through analysis of Odù Ifá, literary texts, oral histories, and popular music, we demonstrate how competing interpretations of culture emerge from selective invocation of Yorùbá epistemologies. Ifá’s ambivalence, we argue, is methodologically generative as it invites an understanding of polygyny inherent in orí, circumstance, and shifting social imaginaries rather than as a uniform cultural mandate. By juxtaposing Ifá’s nuanced portrayals with the distortions reproduced in popular culture, this paper reveals how musicians, novelists, and public discourse often mobilize “culture” to legitimize male privilege, commodify women, and elevate hierarchical domestic arrangements. However, the same cultural field contains women’s counter-narratives from literary critiques to feminist resignifications that unsettle patriarchal readings and articulate alternative moral frameworks. Thus, this paper advances the scholarly conversation by neither romanticising nor pathologising Yorùbá heritage. Instead, it traces polygyny as a dynamic institution shaped by religious hybridity, gendered negotiations, and the enduring Yorùbá philosophical principle of Ọmọlúwàbí (Motadegbe & Ibiyemi, 2025), which holds that virtues and vices coexist. This repositions Ifá as a critical lens for interpreting contemporary gender debates, while offering culturally grounded framework for understanding how Africans themselves grapple with entanglements of tradition, modernity, and justice.